The Court Culture in France, Italy and England in 16-17th Centuries: Interaction and Mutual Influence - Sokolova, Alla (Journal of History Culture and Art Research, 2020)
The article examines the traditions of French court ballet, which are rooted in early medieval Italian musical and theatrical performances, as well as the traditions of the medieval carnival. The functional features of the French court ballet are revealed. French ballet is viewed through the prism of a synthesized art form: dance, music, poetry and complex scenography. It is specified that French ballet as an independent genre was formed in the era of Queen Catherine de Medici. It was revealed that thanks to the skill and professionalism of choreographers of both French and Italian descent, the French court ballet reached its peak in the first half of the seventeenth century. It was determined that the court ballet was becoming a cultural and political instrument that raised the status of France in Europe, served to strengthen the authority of the French monarch, and was a means of uniting the French monarchy and the people. Despite significant financial costs, the political and cultural feasibility of staging court ballets exceeded the economic feasibility. An analogy is drawn with the English court Мasque. It is substantiated that the English court Masque was based on the traditions of Italian intermedio and French court ballet. Thus, English stage designers adopted the experience of Italian stage designers. Dances of Italian origin were an integral part of Masque in England. Choreography in Masque was created by French and Italian choreographers. It has been proven that English culture was influenced by continental culture, which contributed to the formation of a common cultural space. It is substantiated that the genre of French ballet, Italian intermedio and English Masque were not a high art, but over time, having undergone a transformation, they evolved into new forms and genres.